Factors Related to the Activeness of Posyandu Cadres in the Working Area of the Yamo Health Center, Puncak Jaya Regency - Wonda, Osea; Irab, Semuel Piter; Tingginehe, Rosmin M. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to assess the factors associated with the activeness of posyandu cadres in the working area of the Yamo Health Center, Puncak Jaya Regency. The type of research used is quantitative with cross sectional method. The number of respondents was 38 people from 13 Posyandu. The results showed that there was a relationship between age and the activeness of posyandu cadres at the Yamo Health Center (p<0.001). There is no relationship between gender and the liveliness of posyandu cadres at the Yamo Health Center (p>0.46). There is a relationship between education and cadre activeness at the Yamo Health Center (p<0.000). There is no relationship between marital status and cadre activeness at the Yamo Health Center (p>0.147). There is no association between training and cadre activeness at the Yamo Health Center (p>0.200). There is a relationship between incentives and cadre activeness at the Yamo Health Center (p<0.000). There is a relationship between knowledge and cadre activeness at the Yamo Health Center (p<0.001). There is no relationship between attitude and cadre activeness at the Yamo Health Center (p>0.061). As a recommendation, it is necessary to adjust incentives to better suit the expectations and needs of cadres, both in terms of the amount and type of incentives provided.